A comparative analysis of the characteristics of the water removal processes in preparation for incineration of typical wood waste and forest combustible materials; Energy; Vol. 239 - Kuznetsov G. V. Geny Vladimirovich; Nigay N. A. Nataljya Andreevna; Syrodoy S. V. Semen Vladimirovich; Gutareva N. Yu. Nadezhda Yurievna; Malyshev D. Yu. Dmitry Yurievich (2022, 2022)
Title screen